2021
DOI: 10.36253/phyto-12171
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of ‘Italia’ grapevines infected with Esca pathogens

Abstract: Physiological features were examined of a 20-year-old Vitis vinifera ‘Italia’ table grape vineyard cropped in Apulia, Italy. Healthy vines with no foliar symptoms and any indications of wood or berry alterations, vines with natural wood infections by Phaeoacremonium minimum (syn. P. aleophilum) and Phaeomoniella chlamydospora showing brown wood streaking symptoms, and vines naturally infected with P. minimum, P. chlamydospora and Fomitiporia mediterranea with brown wood streaking and white rot symptoms, were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Changes in the plant morphology and physiology, as well as in biochemical functions, were also assessed as possible factors in the development of foliar symptoms. Ascorbate-Glutathione cycle was considered likely to be involved in grapevine susceptibility to fungi associated with the Esca complex [89]. Other hypotheses can contribute for the appearance of leaf symptoms, such as the disturbance of sap flow to the leaves on given xylem pathways altered by fungi, which is described as 'hydraulic dysfunction' [85,90,91], and annual infections by some fungi through pruning or green wounds [23,92]; however, more research is required to develop this hypothesis and to unravel the processes underlying colonization by these fungi [93].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the plant morphology and physiology, as well as in biochemical functions, were also assessed as possible factors in the development of foliar symptoms. Ascorbate-Glutathione cycle was considered likely to be involved in grapevine susceptibility to fungi associated with the Esca complex [89]. Other hypotheses can contribute for the appearance of leaf symptoms, such as the disturbance of sap flow to the leaves on given xylem pathways altered by fungi, which is described as 'hydraulic dysfunction' [85,90,91], and annual infections by some fungi through pruning or green wounds [23,92]; however, more research is required to develop this hypothesis and to unravel the processes underlying colonization by these fungi [93].…”
Section: Discussionmentioning
confidence: 99%
“…Trebbiano, describe a completely different behaviour in response to the viral infection, observing increases in AsA and decreases in DHA, but an unchanged redox state (AsA/DHA ratio). Other researchers have found dissimilar behaviours; Bruno et al [ 80 ] observed a lowered AsA/DHA ratio, while Sgherri et al [ 79 ] described a rise. This different behaviour of AsA in leaves might reflect the different varieties used, the different stages of infection, or even the interaction of phenols and flavonoids with the AsA to act as an H 2 O 2 elimination system [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive surveys conducted worldwide revealed high percentage of infection in propagation material and in grapevine vineyards (Aroca et al., 2010; Carlucci et al., 2017; Dubrovsky & Fabritius, 2007; Liminana et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens associated with black foot disease belong to the genera Campylocarpon , ‘ Cylindrocarpon ’, Dactylonectria and Ilyonectria , based on a recent update of taxonomy (Agustí‐Brisach et al., 2013; Chaverri et al., 2011; Halleen et al., 2006; Lombard et al., 2014). Fungal isolates of the genus Ilyonectria and Dactylonectria associated with black foot disease were initially placed in the genus Cylindrocarpon , with C. destructans being the most frequently reported pathogen (Agustí‐Brisach & Armengol, 2013; Dubrovsky & Fabritius, 2007; Nascimento et al., 2001). Nevertheless, phylogenetic analysis revealed high genetic diversity within fungal isolates associated with black foot disease, which were placed in new genera and species.…”
Section: Introductionmentioning
confidence: 99%